Colonisation Capacity of Vibrio sp. strain Alg 3.1 and Abn 1.2 in the Gastrointestinal Tractof Gnotobiotic Abalone - Faturrahman Faturrahman; Iman Rusmana; Anja Meryandini (Jurnal Penelitian Pendidikan IPA, 2020)
The use of Vibrio strains as probiotics in Indonesia is very rarely reported. The purpose of this study is to select and develop Vibrio probiotic strains that can increase the rate of abalone growth. The ability of bacterial isolates to colonize the abalone digestive tract is one of the important parameters in the selection of probiotic candidates. The research method consisted of 3 main stages namely modification of Vibrio sp isolates to rifampicin mutants, manufacture of gnotobiotic abalone and colonization capacity test. The treatment given in the colonization capacity test is a type of bacteria that consists of Vibrio sp. line Abn1.2RfR, Alg3.1RfR, combination of Abn1.2RfR + Alg3.1RfR, and control without the addition of Vibrio sp. Each type of bacterial treatment was entered in a 10 liter aquarium capacity containing 10 abalone size ± 3.5 cm. Feed in the form of Gracilaria cake containing Vibrio sp. (final concentration of 107 cfu / mL) was given at the beginning of the study. Abalone is observed for 24, 48 and 72 hours without water replacement. Then count the total number of bacteria and the number of agarolytic bacteria. The results showed that the growth characteristics of wild-type Vibrio with mutant Vibrio were not different.Thus it is expected that the use of the two mutant isolates for in vivo testing has the same effectiveness as the wild type.The capacity of colonization of a single isolate or a combination of rifampicin mutant Vibrio continues to decrease with increasing time of observation. Nevertheless, the percentage of mixed isolates remained higher than that of single isolates during the observation time